FIBROMA OF THE TENDON SHEATH-A RARE HAND TUMOR FOLLOWING REPETITIVE TRAUMA TO THE PALM - Yousaf, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Fibroma of the tendon sheath (FTS) is a rare, benign, soft tissue lesion. Clinically, FTS presents similarly to the more common giant cell tumour of the tendon sheath. It can be distinguished histologically by the lack of giant cells, foamy histiocytes and synovial cells. The author presents a case of FTS involving the flexor tendon to the fourth metacarpal following repetitive trauma. A 42 year old man presented with a three year history of painless mass in the right palm that had increased in size and became painful recently. Examination demonstrated 6Ã—4 cm firm, nodular, superficial mass that was adherent to the underlying structures. Radiographs revealed soft tissue mass. Ultrasound showed a solid heterogeneous mass and the MRI demonstrated that the mass cantered predominantly at the mid and distal portion of fourth metacarpal. Fine Needle Aspiration Cytology was inconclusive. The patient underwent excisional biopsy of the lesion showing lobulated lesion closely resembling hyalinized collagen. Neither vascular proliferations, necrosis, nor mitoses were observed. A diagnosis of FTS was made. The case report  provided an additional rare case to literature of a FTS and highlights the need to consider this entity in the differential diagnosis of any soft tissue lesion in the hand after repetitive trauma. Two months later the patient demonstrated full range of movements in the hand